Urinary excretion of calcium and phosphate in dogs with pituitary‐dependent hypercortisolism: case control study in 499 dogs. (19th December 2015) - Fracassi, F.; Malerba, E.; Furlanello, T.; Caldin, M.
Abstract : Pituitary‐dependent hypercortisolism (PDH) in dogs is frequently associated with high serum phosphate and parathormone concentrations which are in turn associated with prognosis and clinical presentation. The pathogenesis of such abnormalities remains unknown. The aim of the present study was to evaluate the serum and urinary concentrations and the urinary fractional excretion of phosphate and calcium in dogs with PDH. Medical records of newly diagnosed PDH dogs before treatment from one referral centre were retrospectively evaluated. One clinically normal and one sick dog for each dog with PDH were included as controls. One hundred and sixty‐seven dogs with PDH were included. The serum phosphate concentration in PDH dogs was significantly (P<0.0001) higher compared with clinically normal control dogs (CNDs) and sick control dogs (SCDs). The serum calcium concentration in PDH dogs was significantly higher compared with SCDs but not different compared with CNDs. Urinary fractional excretion of phosphate in PDH dogs was significantly lower compared with CNDs and SCDs. Urinary fractional excretion of calcium in PDH dogs was significantly higher compared with CNDs and SCDs. In conclusion, PDH dogs have lower phosphaturia and higher calciuria compared with control dogs. These findings suggest that, at least in part, high serum phosphate concentrations are related to the renal retention of phosphate.